Humor styles and personality: A systematic review and meta-analysis on the relations between humor styles and the Big Five personality traits. (1st February 2020) - Plessen, Constantin Y.; Franken, Fabian R.; Ster, Christoph; Schmid, Rebecca R.; Wolfmayr, Christoph; Mayer, Anna-Maria; Sobisch, Marc; Kathofer, Maximilian; Rattner, Katrin; Kotlyar, Elona; Maierwieser, Rory J.; Tran, Ulrich S.
Abstract: Health-promoting and health-endangering humor styles as measured with the Humor Styles Questionnaire have been repeatedly associated with personality traits. Yet, a comprehensive meta-analysis of all currently available studies on this topic as well as an exploration of the highly heterogeneous effect sizes found in this literature is still missing. We provide an updated overview of the literature, synthesize its results in a random effects model meta-analysis, and explore possible moderators. An extensive literature search identified 24 studies from 13 countries ( N  = 11, 791). Health-promoting humor styles were positively correlated with extraversion, agreeableness, conscientiousness, and openness, and negatively correlated with neuroticism. Health-endangering humor styles were positively associated with neuroticism and negatively associated with agreeableness and conscientiousness. Between-study heterogeneity ranged from I 2  = 41% to 96% and could be only partially explained by moderator variables. The effects appear robust with respect to individual studies, publication bias, and measurement error, and appear mostly generalizable across sexes, sample composition, and continent. Further research is required to examine these associations in less developed countries, possible moderators for the high amount of effect size heterogeneity, and the development of these associations across the lifespan.